Qualitative Research in Applied Linguistics: A Practical Introduction, edited by Juanita Heigham and Robert Croker - Kamran Akhtar Siddiqui; Bahawal Soomro; Rashid Hussain Abbasi; Usama Abdul Rehman; Aizaz Soomro (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
This review makes a point in favor of the assertion made for the book that it is a practical introduction to the qualitative research in applied linguistics. The book consists of four parts: an overview of qualitative research, qualitative research methods, qualitative data collection methods, ethical practice issues and the writing of research reports. After proving a rich introduction to the qualitative research, the book discusses qualitative research approaches using a reader-friendly and interactive structure: pre-reading and post-reading questions along with the list of further readings. Then the data collection tools have been thoroughly discussed. What makes this book more useful is the use of illustrative examples for each qualitative research approach and data collection tool. The last part discusses core issues of ethics and drafting a research report. From the perspective of a novice researcher, it has achieved the goal of educating readers about qualitative research methods and data collection tools, as it gradually tracks the reader and provides them with a linking concept for a better understanding. However, reference to one study for both ethnography and case study remains a confusing point. Besides, the review suggests addition of some images to make reading of the book more interesting, especially for visual learners. Besides, a diagram should be given at the end of research methods chapters to outline the steps taken by researchers to do their studies.